Enhancing sensitivity in flexible MEMS capacitive pressure sensors: a review - Hajizi, H. M. M.; Aris, H.; Ismail, M. H.; Nor, N. I. M.; Nordin, Anis Nurashikin; Jamel, N.; Johari, S.; Aziz, A. A. (IOP Publishing Ltd, 2025)
vancements focus on material innovations like graphene and silver nanowires, structural designs such as pyramidal microstructures and interdigitated electrodes, and fabrication techniques like laser-induced graphene and multilayer architectures. These approaches improve sensitivity, broaden detection ranges, and enhance response times. Despite progress, challenges in stability and fabrication complexity remain. This review summarises current strategies, offering insights into advancing sensor performance for emerging applications.